Fatigue Life Comparative Analysis of Rolling-sliding Bearing based on nCode DesignLife - Lu Liming; Yu Yunyun; Zeng Guowen (Jixie chuandong)
The finite element model of the static mechanics simulation result of rolling- sliding bearing is uses as a model for fatigue analysis,and the load cycle variable of the fatigue analysis is the time stress variation law of the dynamic simulation results of rolling- sliding bearing. The fatigue life simulation of cylindrical roller bearing and rolling- sliding bearing is carried out by using the n Code Design Life fatigue analysis software,the cloud picture of life and damage of two kinds of bearing are got,the parts easily damaged of two kinds of bearing are determined from the cloud picture. The fatigue life test of two kinds of bearings is carried out on the experimental machine,and under the premise of meeting the fatigue strength,concluded that the damage of the parts of the rolling- sliding bearing is less and the anti fatigue ability is stronger. Therefore,the rolling- sliding bearing has higher reliability performance.